ANSWER
The rule is given by the relation,
![y = 2x + 1](https://tex.z-dn.net/?f=y%20%3D%202x%20%2B%201)
EXPLANATION
We need to check and see if there is a constant difference between the y-values.
![1 - - 1 = 2 = 3 - 1](https://tex.z-dn.net/?f=1%20-%20%20-%201%20%3D%202%20%3D%203%20-%201)
We can see that, there is a constant difference of 2.
This means that the table represents a linear relationship.
Let the rule be of the form,
![y = mx + c](https://tex.z-dn.net/?f=y%20%3D%20mx%20%2B%20c)
Then the points in the table should satisfy the above rule.
So let us plug in
![(0,1)](https://tex.z-dn.net/?f=%280%2C1%29)
This implies that,
![1 =m (0) + c](https://tex.z-dn.net/?f=1%20%3Dm%20%280%29%20%2B%20c)
![1 = 0 + c](https://tex.z-dn.net/?f=1%20%3D%200%20%2B%20c)
![c = 1](https://tex.z-dn.net/?f=c%20%3D%201)
Our rule now becomes,
![y = mx + 1 - - (1)](https://tex.z-dn.net/?f=y%20%3D%20mx%20%2B%201%20-%20%20-%20%281%29)
We again plug in another point say, (-1,-1) in to equation (1) to get,
![- 1 = m( - 1) + 1](https://tex.z-dn.net/?f=%20-%201%20%3D%20m%28%20-%201%29%20%20%20%2B%201)
we solve for m now to obtain,
![- m=-1-1](https://tex.z-dn.net/?f=%20-%20m%3D-1-1)
![- m = - 2](https://tex.z-dn.net/?f=%20-%20m%20%3D%20%20-%202)
![m = 2](https://tex.z-dn.net/?f=m%20%3D%202)
We now substitute back in to equation (1) to get
Answer:
Step-by-step explanation:
C
Answer:
I have made it in above pic
59
Step-by-step explanation:
7 × 5 = 35
6 × 4 = 24
35 + 24 = 59
because 4 + 5 is 9 and 3 + 2 is 5
so 59